SIMULATION STUDY ON OPENING MECHANISM OF THERMALMECHANICAL CRACK OF BRAKE DISC - NI Jing; SHI LiFeng; ZHENG LingNan; YANG Xiao (Jixie qiangdu)
Considering physical properties variation of gray cast iron with temperature,difference mechanical behavior of material between compression and tension,relationship of elastic and plastic stress-strain of material,synthetically studied the temperature field,stress field,strain field and thermal crack strength of brake disc under different braking conditions,and revealed the opening mechanism of thermomechanical crack and crack distribution. Results of thermomechanical coupling simulation show the maximum temperature is 360℃ with initial speed of 180km/h,radial compression/tension stress are275Mpa/85 Mpa,circumferential compression/tension stress are 374 MPa/100 MPa,radial/circumferential plastic deformation are-4. 6 × 10-5/-6. 75 × 10-5. Results of thermomechanical opening calculation show stress intensity factor of radial crack ΔK6. 69 MPa·m1/2is larger than ΔK 5. 49 MPa·m1/2of circumferential crack,opening displacement of radial crack is larger than that of circumferential crack,which indicating radial cracks are mainly distributed on brake disc,and the sizes of radial crack are larger than that of circumferential crack.